Incidental finding of thoracic outlet syndrome in a case of right tubal ruptured ectopic pregnancy - Chavan, Niranjan; Mahapatra, Shalini; Ruhil, Meenakshi; Mohokar, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
A 30-year-old woman, (multigravida) suffering from lower abdominal pain and slight vaginal bleeding was transferred to our hospital. She came with a pelvic ultrasound report. The provisional diagnosis of right tubal ectopic pregnancy was made. A laparotomy was carried out. Intraoperatively, blood pressure in both the arms were taken which revealed different blood pressure in different arms. A diagnosis of thoracic outlet syndrome was made. No postoperative complications were observed.